Vulnerability and risk situations self-reported by adolescent students - Queiroz, Maria Veraci Oliveira; Franco, Jacirene Gonçalves Lima; Cavaleiro, Laura Martins Mendes; Brasil, Eysler Gonçalves Maia (Rev Rene, 2013)
One aimed to characterize the profile of adolescents regarding their socio-demographic aspects and describe the risk and vulnerability situations mentioned by them. This is a descriptive and quantitative study carried out with 500 school adolescent students aged between 13 and 19 years old, from the city of Iguatu-CE, Brazil. One applied a questionnaire in the school in August 2008. Data were analyzed using a statistical program. The results showed that adolescents were predominantly from the urban area (59.25%); females (60.0%), most interviewees reported living with their parents (84.6%) and had income less than or equal to a minimum wage (64.2%). The use of licit and illicit drugs was identified as a factor that exposes adolescents’ health to risks (59.2%), and they considered the prevention important (18.2%), including healthy eating habits (15.2%). The adolescents saw the risks present in daily life and the possibilities of prevention through education in the family and school environment. DOI: https://doi.org/10.15253/2175-6783.2013000300005